(untitled) (Research, Society and Development, 2020)
The use of competitiveness indicators to evaluate the performance of tourist destinations has enabled the identification of weaknesses and potentialities that need to be addressed by public policies to promote the sector. However, in the case of Brazil and considering that the existing regional specificities generate their own dynamics for the development of the activity, it was considered appropriate to conduct, in this article, an analysis that considered performance patterns that could subsidize specific incentive policy sets. This is an exploratory study with a quantitative basis that resorted to the use of hierarchical and non-hierarchical statistical methods, as well as the analysis of variance to create clusters of municipalities, based on the thirteen dimensions evaluated by the National Tourism Competitiveness Index, designed by the Ministry of Tourism, Sebrae and Getulio Vargas Foundation. In conclusion, we identified three groups of municipalities with different levels of competitiveness, strongly based on parameters associated with the level of dynamism of their economies, having in common a major deficiency regarding the level of Regional Cooperation. In addition, there was a common need to all destinations related to the availability of statistical analyzes and studies on the sector.